Harnessing community conversations for gender-responsive engagement in livestock management in Ethiopia: a methodological reflection - Lemma, Mamusha; Alemu, Biruk; Knight-Jones, Theodore J.D. (Frontiers Media, 2025)
Background: Participatory approaches are increasingly employed to design context-specific interventions that are more inclusive, responsive, and effective. The Community Conversation (CC) approach has been tailored to Ethiopia’s livestock management context. As part of the Consultative Group on International Agricultural Research Program on Livestock (CRP Livestock), gender-responsive CC materials on livestock management have been developed and implemented across various rural communities to raise awareness and derive community-led actions. This paper explores how CCs were harnessed through improvisation and provides insights for practitioners to strategically adapt the approach in diverse contexts to foster gender-responsive community engagement.